Pengembangan Sistem Perhitungan Posisi Tampak Bulan pada Koordinat Ekuatorial berbasis Python - Wandira, Cintha Ayu; Pramudya, Yudhiakto (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
In the field of astronomy, it is important to know the position of the moon in equatorial coordinates. However, these calculations can be difficult to do manually. Therefore, a system for calculating the visible position of the moon in Python-based equatorial coordinates has been developed. This system uses a suitable algorithm to calculate the visible position of the moon in equatorial coordinates. The calculation results obtained from this system are then compared with the simulation results from the Stellarium software. System for calculating the visible position of the moon in equatorial coordinates with PythonRA values (alpha): 11h21m36.9s and declination (delta): 8Â° 28' 23â€ while the results from the Stellarium software simulation at the same time are RA (alpha): 11h18m0.33s and declination (delta): 8Â° 25' 18.2â€.The results of the comparison show that the system for calculating the visible position of the moon in Python-based equatorial coordinates has a difference in RA of 0h3m36s and declination of 0Â°3'4.8â€ from the Stellarium simulation. The error value for the comparison of python calculations with Stellarium is RA = 2% and Declination = 0.6%. This shows that the use of python can simplify calculations with difficult algorithms and the results obtained are quite accurate. Thus, this Python-based system for calculating the visible position of the moon in equatorial coordinates can be used as a tool in the field of astronomy.